CLARIFY and Its Relevance to the Caribbean Population - Jacobson, Anne (MD Conference Express, 2010)
The Prospective Observational Longitudinal Registry of Patients with Stable Coronary Artery Disease [CLARIFY] study is a large (n=31,040) international trial that is aimed at evaluating outcomes and long-term prognostic determinants in outpatients with stable coronary artery disease, including heart rate, that adequately represent this contemporary population worldwide. This article discusses the significance of the CLARIFY trial as it applies to the Caribbean.